Airway Management in Pediatric Patients: Cuff-Solved Problem? - Eva Klabusayová; Jozef Klučka; Milan Kratochvíl; Tereza Musilová; Václav Vafek; Tamara Skříšovská; Jana Djakow; Martina Kosinová; Pavla Havránková; Petr Štourač (Children, 2022)
Traditionally, uncuffed tubes were used in pediatric patients under 8 years in pursuit of reducing the risk of postextubation stridor. Although computed tomography and magnetic resonance imaging studies confirmed that the subglottic area remains the narrowest part of pediatric airway, the use of uncuffed tubes failed to reduce the risk of subglottic swelling. Properly used cuffed tubes (correct size and correct cuff management) are currently recommended as the first option in emergency, anesthesiology and intensive care in all pediatric patients. Clinical practice particularly in the intensive care area remains variable. This review aims to analyze the current recommendation for airway management in children in emergency, anesthesiology and intensive care settings.